1997
DOI: 10.1017/s0021859697004309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on growth, shoot water relations and root hydraulic conductivity in tomato plants

Abstract: Growth, shoot water relations and root hydraulic conductivity were studied in tomato plants (Lycopersicon esculentum cv. INCA9) subjected to different salt concentrations in the root medium. Two experiments were carried out at Instituto Nacional de Ciencias Agrı! colas (INCA), Cuba, during May and June 1995. In the first experiment, plants were grown for 13 days in a nutrient solution with 0 or 100 m NaCl. In the second experiment, the hydraulic conductivity was measured on roots submerged in nine different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 12 publications
2
32
1
1
Order By: Relevance
“…This observation was confirmed for Bell Pepper seedlings (Morales-Garcia et al, 2008) which could be a consequence of a higher accumulation of Na+ in roots than in shoots (Blom-Zandstra et al, 1998). Decreasing in the root/shoot ratio have also been reported for other seedlings grown under saline conditions (Al-Harbi, 1995;Rodriguez et al, 1997;Yildirim and Guvenc, 2006). Salinity reduces root development, water uptake as well as transpiration and respiration which results in perished hormonal balance, altered photosynthesis rate, decreased nitrate uptake, and cell growth.…”
Section: Effect Of the Water Typesupporting
confidence: 62%
“…This observation was confirmed for Bell Pepper seedlings (Morales-Garcia et al, 2008) which could be a consequence of a higher accumulation of Na+ in roots than in shoots (Blom-Zandstra et al, 1998). Decreasing in the root/shoot ratio have also been reported for other seedlings grown under saline conditions (Al-Harbi, 1995;Rodriguez et al, 1997;Yildirim and Guvenc, 2006). Salinity reduces root development, water uptake as well as transpiration and respiration which results in perished hormonal balance, altered photosynthesis rate, decreased nitrate uptake, and cell growth.…”
Section: Effect Of the Water Typesupporting
confidence: 62%
“…Thus, the mean values reached 260,00 mg/g FW (Figure 2). Also, the lowest values for the content of the carotenoids were marked in the levels 10g/l with 0,354 mg/g FW and at 15 g/l NaCl with 0,267 mg/g FW (Figure 3 As accessory pigments, carotenoids participate in photoinduced electron transfer processes and protect chlorophyll photoxidative damage (Rodriguez et al, 1997). The decrease of total carotenoids content (TCC) may be explained as a result of either a low synthesis rate or enhanced degradation induced by reactive oxygen species (ROS).…”
Section: Chlorophyll (A B) and Carotenoids Contentmentioning
confidence: 99%
“…A strong linear relationship (r = 0.97) between EC of the nutrient solution and tomato plant water absorption has been demonstrated [170]. For other species, it has been suggested that root permeability decreased under salt stress and might explain the reduction of water uptake [64,152], but this explanation is not conclusive for tomato grown under 0-200 mM NaCl [158,162]. Tomato fruit has a very low transpiration rate and only around 15% of the water input comes via the xylem [90].…”
Section: Effect Of Electrical Conductivity Of the Nutrient Solution Omentioning
confidence: 99%